Lipólisis de queso tipo fresco y quesos madurados (quesos azules), factores que afectan y consecuencias - Quevedo Barreto, Luci Angelita (2021)
This research aims to compare the lipolysis of fresh type cheese and ripened cheeses (blue cheeses). Factors that affect and consequences this process of lipolysis in cheeses are significant biochemical changes, especially in ripened cheeses. This process is a degradation of the fat produced by the enzymatic way. This literature review was analyzed using the PRISMA statement, which consists of a systematic review that is carried out in 4 steps; identification, Screening, Selection, and inclusion. As a result of the bibliographic research, it is mentioned that lipolysis in fresh type cheeses can be produced by inadequate thermal control at the moment of pasteurization of the milk, handmade elaboration. By the milk's lipases, this biochemical process in fresh type cheeses produces oxidation and rancidity in them, causing a bad quality in the product. On the other hand, it is concluded that lipolysis in ripened cheeses is induced by multiple factors such as the milk's quality, the degree of agitation, homogenization, pH, concentration, pasteurization, ripening time, and temperature. Besides, the FFA produced in these types of cheeses is the one that enhances the characteristic flavor and aroma. Knowledge of the factors that influence the lipolysis process facilitates cheese producers to better control the elaboration processes